The Use of English in Video Promotion of Elsotel Purwokerto in Instagram - Kintani Khansa Marwa (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2023)
Elsotel Purwokerto has uploaded lots of interesting promotional content on Instagram and Facebook. It was found that Elsotel Purwokerto does not yet have a promotional video to properly introduce their hotel, such as explaining what types of rooms are available, facilities, restaurants, parking areas and the ambience. Therefore the writer makes a promotional video that explains the contents of Elsotel Purwokerto in more detail and more properly. This can help Elsotel Purwokerto to provide information to tourists who want to stay at Elsotel Purwokerto with more detailed information through the videos that have been made. Even though it has several obstacles such as unfriendly weather or too crowded people, the writer can overcome all of these